Policy Implementation in Handling Stunting in Bangkalan Regency - Arini, Yeny Yustia; Handoko, Rudy; Maruta, Anom (International Journal Labs, 2025)
This research examines the implementation of stunting handling policies in Bangkalan Regency, focusing on Regent Regulation No. 6 of 2019. Using a descriptive qualitative approach, data was collected through activity documents, interviews, and observations. The findings reveal that while the policy has led to some successes, such as reducing stunting rates and improving child nutrition through collaborative efforts between health workers, the community, and local government, challenges remain. These include uneven economic empowerment, limited public awareness about maternal and child nutrition, insufficient private sector support, and underutilized local potential. The research highlights the need for a collaborative implementation model to address these gaps and ensure sustainability. Key recommendations include enhancing cross-sector collaboration, increasing public awareness campaigns on health and nutrition, and fostering stronger private sector engagement. The proposed model emphasizes continuous monitoring and policy adaptation to maintain progress in reducing stunting rates. By addressing these areas, the research underscores the importance of a holistic and sustainable approach to tackling stunting in Bangkalan Regency.